2016
DOI: 10.1038/srep39149
|View full text |Cite
|
Sign up to set email alerts
|

Human cellular CYBA UTR sequences increase mRNA translation without affecting the half-life of recombinant RNA transcripts

Abstract: Modified nucleotide chemistries that increase the half-life (T1/2) of transfected recombinant mRNA and the use of non-native 5′- and 3′-untranslated region (UTR) sequences that enhance protein translation are advancing the prospects of transcript therapy. To this end, a set of UTR sequences that are present in mRNAs with long cellular T1/2 were synthesized and cloned as five different recombinant sequence set combinations as upstream 5′-UTR and/or downstream 3′-UTR regions flanking a reporter gene. Initial scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…1). Our results prove the concept of this approach and significantly increase protein production compared to the UTRs reported in the literatures 12,[16][17][18] . Lastly, a series of potential SARS-CoV-2 antigens are visualized via fluorescent imaging in both cell and animal models, which may serve as vaccine candidates for the clinical trials.…”
Section: Introductionsupporting
confidence: 84%
See 2 more Smart Citations
“…1). Our results prove the concept of this approach and significantly increase protein production compared to the UTRs reported in the literatures 12,[16][17][18] . Lastly, a series of potential SARS-CoV-2 antigens are visualized via fluorescent imaging in both cell and animal models, which may serve as vaccine candidates for the clinical trials.…”
Section: Introductionsupporting
confidence: 84%
“…The mRNAs encoding Firefly luciferase were synthesized with these 5' UTRs and were delivered to Hep3B and 293T cells using lipofectamine 3000. The control UTRs include CYBA UTRs (named CYBA) 12 , alpha globin UTRs (named AG) 13 , and modified alpha globin UTRs (AG+G with a complete Kozak sequence and 5AG+G without 3' UTR) 18 . 5' UTR from S27a-44 was better than that from S27a-45 ( Fig.…”
Section: Endogenous 5' Utr From Bioinformatics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It was also shown that the 3 0 UTR of human b-globin arranged in a head-to-tail orientation additionally increases mRNA stability. 3,27,28 Coding sequence: the coding sequence also influences the translational efficiency, since it is known that there exist preferred codons that lead to an optimized and accelerated translation compared to rare codons. 29 Moreover, nucleotide modification is another tool to improve mRNA translation by improving its stability and reducing its immunogenicity.…”
Section: The Concept Of Mrna Therapymentioning
confidence: 99%
“…Compared to classical gene therapy with DNA-based vectors, use of mRNA offers several advantages, such as transient expression (Kapeli and Yeo 2012;Lodish 2012), lack of necessity to enter the nucleus, and no risk of chromosomal integration (Cannon and Weissman 2002;Hacein-Bey-Abina et al 2003;Bernal 2013). After overcoming the intrinsic limitations of the mRNA, namely immunogenicity and instability, using chemically modified nucleotides (Karikó et al 2005(Karikó et al , 2008Kormann et al 2011), researchers have significantly improved the mRNA molecule by optimizing the structural elements, namely cap (Grudzien-Nogalska et al 2013;Ziemniak et al 2013;Kowalska et al 2014), 5 ′ -and 3 ′ -UTRs (Ferizi et al 2016;Schrom et al 2017;Trepotec et al 2018), and coding sequence(s) (Thess et al 2015;Schrom et al 2017). Increasing its stability and translational yields has led to a progress from the first use of encoding a potentially therapeutic protein (Wolff et al 1990) to preclinical (Bahl et al 2017;Richner et al 2017) and clinical applications (Mullard 2016).…”
Section: Introductionmentioning
confidence: 99%